Amorphous microwires of high entropy alloys with large magnetocaloric effect. (May 2018) - Sheng, Wei; Wang, Jun-Qiang; Wang, Gang; Huo, Juntao; Wang, Xinmin; Li, Run-Wei
Abstract: Microwires of Gd20 Ho20 Er20 Al20 TM20 (TM = Fe, Co and Ni) high-entropy metallic glasses (HE-MGs) are successfully fabricated by a melt-extraction method, which exhibit good magnetocaloric properties. The maximum magnetic entropy change and refrigerant capacity under 5 T of the Gd20 Ho20 Er20 Al20 Co20 HE-MG microwire can reach 10.2 J kg −1 K −1 and 625 J kg −1, respectively. In addition, the magnetocaloric properties of the HE-MG microwires can be widely tuned by doping different transition metals. The HE-MG microwires combining high heat-exchange efficiency and excellent mechanical properties are attractive candidates for applications in magnetic refrigeration. Graphical abstract: High-entropy metallic glass microwires with good magnetocaloric properties are successfully fabricated by using melt-extraction method. Highlights: Microwires of high-entropy metallic glass (HE-MG) are successfully fabricated using melt-extraction method. HE-MG microwires exhibit good magnetocaloric properties. The magnetocaloric properties of the HE-MG microwires can be widely tuned by doping different transition metals. HE-MG microwires are attractive candidates for applications in magnetic refrigeration.